Brain SPECT in dementia a clinical-scintigraphic correlation SPECT cerebral na demência: uma correlação clínico-cintilográfica - Carlos A. Buchpiguel; Sandra C. Mathias; Liliam Y. Itaya; Nélio G. Barros; Luis A.P. Portela; Jose M. M. Freitas; Paulo Caramelli; Paulo E. Carrilho; Luiz A. Bacheschi; Fausto H Hironaka; Ricardo Nitrini (Arquivos de Neuro-Psiquiatria)
The aim of this study was to compare the accuracy of computed tomography (CT) and single photon emission computerized tomography (SPECT) in the diagnosis of dementia. Fifty-two patients with clinical diagnosis of dementia and 11 controls were studied. The scans were interpreted by one experienced neuroradiologist and one nuclear radiologist, both blinded to the clinical data. In the diagnosis of dementia, CT and SPECT showed equal sensitivity (82.7%) and statistically similar specificity (63.8 and 81.8%, respectively). The specificity of SPECT in diagnosing Alzheimer's disease (100%) was statistically superior to CT (69%). However, both methods showed similar sensitivity in detecting Alzheimer's disease. In conclusion, SPECT and CT showed similar accuracy in the diagnosis of dementia. The quite high specificity of SPECT in Alzheimer's disease may be useful for confirming that diagnosis, particularly for patients with presenile onset of the disease. O objetivo deste estudo foi comparar a acurácia da tomografia computadorizada (TC) e da tomografia computadorizada por emissão de fóton único (SPECT) no diagnóstico de demência. Cinquenta e dois pacientes com diagnóstico clínico de demência e 11 controles foram estudados. Os exames foram interpretados por um neuroradiologista e um radiologista nuclear, ambos cegos quanto aos dados clínicos. No diagnóstico de demência, a TC e a SPECT mostraram sensibilidades iguais (82,7%) e estatisticamente especificidades semelhantes (63,8 e 81,8%, respectivamente). A especificidade da SPECT no diagnóstico da doença de Alzheimer (100%) foi significativamente superior à da TC (69%). Contudo, ambos os métodos mostraram sensibilidades semelhantes na detecção de doença de Alzheimer. Em conclusão, TC e SPECT mostraram acurácia similar no diagnóstico de demência. A alta especificidade observada no diagnóstico de doença de Alzheimer pode ser útil na confirmação do diagnóstico clínico, especialmente na forma pré-senil da doença.